Pengaruh Kualitas Produk Dan Citra Merek Terhadap Keputusan Pembelian Dan Dampaknya Pada Kepuasan Konsumen Produk Skintific Di Cikarang - Nurlina, Nurlina; Wulandari, Anna (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
In its role as a benchmark for how a scientific product becomes superior and competitive in the market, of course it results from the product quality, brand image and promotion of a product that is prepared. The aim of this research is to determine the influence of Product Quality and Consumer Satisfaction on Purchasing Decisions and its impact on consumer satisfaction as a mediating variable. This research uses quantitative methods with a sample size of 100 respondents. This research was processed using SmartPLS and data collection was carried out via Google forms. Product quality has a significant effect on purchasing decisions with a value of 3.679. Product Quality has no effect on Consumer Satisfaction which has a value of 1.509. Consumer Satisfaction has a significant effect on Purchasing Decisions with a value of 2.987. The Brand Image variable has a significant effect on Purchasing Decisions with a value of 3.303. Brand Image influences consumer Satisfaction with a value of 4.104. Product Quality has no effect on Consumer Satisfaction and Purchasing Decisions has a value of 1.457. Brand Image has a significant effect on Consumer Satisfaction and Purchasing Decisions with a value of 2.108.